The Effect of Brand Image and Product Quality on Consumer Loyalty of Ventela Shoe Products Through Consumer Satisfaction Variables - Fakhira Azzahra; Putu Nina Madiawati (International Journal of Economics Development Research (IJEDR), 2024)
Fashion has become an important element in everyday life, especially for millennials who often showcase their style on social media. The styles of clothing and accessories on display often become trends. As a result, fashion companies continue to innovate to meet the growing needs of consumers. In Indonesia, there are many local brands, including shoe brands. One of them is Ventela shoes, which are local shoes from Bandung. The purpose of this study is to determine how much influence brand image and product quality have on consumer loyalty for Ventela shoe products through the variable of customer satisfaction. This study uses a quantitative approach, with the number of respondents in this study being 96 people. Analysis using non-probability sampling method with purposive sampling technique. Data collection using a questionnaire distributed via Google Form. The data analysis technique uses SEM PLS with the help of SmartPLS 3.2.9 software. Based on the results of this study, the brand image variable has a significant effect on customer satisfaction, product quality has a significant effect on customer satisfaction, brand image has a significant effect on customer loyalty, product quality has a significant effect on customer loyalty, customer satisfaction has no significant effect on customer loyalty, brand image has a significant effect on customer loyalty through customer satisfaction, and product quality has no significant effect on customer loyalty through customer satisfaction.